2006
DOI: 10.1007/s00122-006-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of the pear scab resistance gene Vnk of Japanese pear cultivar Kinchaku

Abstract: Pear scab (caused by Venturia nashicola) is one of the most harmful diseases of pears, especially Japanese and Chinese pear species. The molecular identification and early selection of resistant plants could greatly improve pear breeding. We have identified the position of the scab resistance gene, designated Vnk in an indigenous Japanese pear cultivar Kinchaku, within the pear genome by using simple sequence repeat (SSR) markers derived from pear and apple. The position of Vnk was identified in the central re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 39 publications
2
49
0
1
Order By: Relevance
“…In this study, we analyzed 5 DNA markers linked to the 'Kinchaku' Vnk scab resistance reported in Terakami et al (2006) to two populations of the progenies, and confirmed the results with a standard V. nashicola inoculation test.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…In this study, we analyzed 5 DNA markers linked to the 'Kinchaku' Vnk scab resistance reported in Terakami et al (2006) to two populations of the progenies, and confirmed the results with a standard V. nashicola inoculation test.…”
Section: Introductionsupporting
confidence: 65%
“…A RAPD marker linked to a gene for susceptibility to pear black spot disease was reported (Banno et al, 1999;Iketani et al, 2001) and the gene was mapped on linkage group (LG) 11 50 (Terakami et al, 2007). The scab resistance gene (Vnk) from 'Kinchaku' was mapped in the central region of LG1 (Terakami et al, 2006;Yamamoto et al, 2004). Terakami et al (2006) reported one SSR and 5 STS markers closely linked to Vnk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, detection of the physical locations of useful gene loci has progressed in important crops and vegetables (Iwano et al, 1998;Ohmido et al, 1998). Therefore, physical mapping of useful genes, such as for scab resistance and black spot disease susceptibility (Terakami et al, 2006, should be conducted in pears. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, physical mapping of useful genes, for instance, scab resistance and black spot disease susceptibility in pear (Terakami et al, 2006, should be conducted.…”
Section: Conclusion and Perspectivementioning
confidence: 99%